Atividades agrícolas e não agrícolas no meio rural da Amazônia Legal: uma análise a partir dos microdados do censo demográfico de 2010 - Machado, Paulo Vinícius Farina (2013)
This research has focused to the recent dynamics of rural Brazil where activities related to non-agricultural occupations have shown an increasing importance face to agricultural occupations, in terms of absorption of labor as the production yields. This work is performed at region level characterized by the states that compound the Legal Amazon. This research takes into account issues related to education level, job category, types of activities, and income. In order to be found in non-agricultural activities better conditions relating to income, higher levels of education, less income discrepancies between genders, besides the fact that the sum of total income in the non-agricultural sector is almost the same to those provided by the agricultural sector. The work also proposes to conduct an analysis of a number of cities classified according to their income distribution through the well known Gini coefficient, in order to find evidence of the importance of non-agricultural activities face to the agricultural counties. This fact is observed in different cities since the average income of individuals allocated to the non-agricultural sector has less variation compared to those involved in the agricultural sector.